CROSS-CULTURAL COMMUNICATION: VIEWING THE NEO-RACISM CLIMATE IN INDONESIA IN THE NEW MEDIA ERA - al-Mujtahid, Nazil Mumtaz (Hikmah, 2023)
This article intends to describe the climate of neoracism in Indonesia, particularly in the age of new media. The emergence of new media in human existence has resulted in numerous social transformations, including the phenomenon known as neo-racism. Neoracism is a difficult problem to identify because it is more elusive than racism. This research is urgently needed to identify neo-racism in order to reduce social segregation, particularly in the age of new media. In the age of new media, this study employs a qualitative, sociological methodology. The author collects data by conducting interviews and observing social media users on Twitter. This study's primary data consists of Twitter sources and digital footprints. While the secondary data used in this study is a literature review comprised of various scientific books and articles, this is a review of the secondary literature. The original data is then analysed using techniques for content analysis. The results of the study indicate that the extent of neo-racism in Indonesia is greater than the public is aware of. Various regulations and netizens' criticism of the rejection of neo-racism have been devised, but this strategy has been ineffective due to the rise of neo-racism in the age of new media.